PENGUATAN LITERASI BERBAHASA INDONESIA DENGAN GERAKAN LITERASI SEKOLAH PADA SISWA SMP - Selvia Yuliana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Abstract Indonesian language literacy needs to be instilled in junior high school students by paying attention to their listening, reading, speaking and writing skills so that they are skilled in language. The meaning of literacy has progressed so as to require students to practice critical thinking. The purpose of this study is to improve literacy skills in Indonesian in junior high school students by implementing GLS. The problems examined in the study are examining students interest in reading and difficulty understanding the contents of the book. Research conducted using descriptive qualitative methods that describe the results of strengthening Indonesian-language literacy with GLS in SMPN 2 Cimahi. The technique of collecting data is done through observing students reading activities every day for 15 minutes. The results showed that strengthening Indonesian language literacy with GLS was able to improve language literacy in terms of students iinterest in reading and critical understanding.Keywords: Strengthening literacy, GLS, junior high school students